Equatorial Undercurrent Influence on Surface Seawater δ18O Values in the Galápagos - Conroy, Jessica L.; Murray, Nicole K.; Patterson, Gillian S.; Schore, Aiden I. G.; Ikuru, Ima; Cole, Julia E.; Chillagana, David; Echeverria, Fernando (PO.DAAC, CA, USA, 2023)
Stable isotopes of oxygen (δ18O) in seawater reflect the combined influences of ocean circulation and atmospheric moisture balance. However, it is difficult to disentangle disparate ocean and atmosphere influences on modern seawater δ18O values, partly because continuous time series of seawater δ18O are rare. Here we present a nearly nine-year, continuous record of seawater δ18O values from the Galápagos. Seawater δ18O values faithfully track sea surface salinity and salinity along the equator at 50 m depth. Zonal current velocity within the Equatorial Undercurrent (EUC), directly west of the Galápagos, is strongly correlated with Galápagos surface seawater δ18O values with a 1-month lag. Reconstructions of Galápagos seawater δ18O values could thus provide a window into past variations in the strength of the EUC, an important influence on large-scale tropical Pacific climate.Plain Language SummaryThe Equatorial Undercurrent (EUC) flows beneath the surface of the equatorial Pacific Ocean from west to east, transporting cold, salty, nutrient rich waters. When this current hits the Galápagos, it rises to the surface. Its high nutrient levels serve as the foundation for the diverse Galápagos ecosystem and its colder temperature helps set up a strong sea surface temperature gradient that is the foundation of the tropical Pacific climate system. Despite its importance, little is known about how this current has varied prior to the short period of instrumental observations, and it remains challenging to reproduce in climate models. Here we show how Galápagos seawater stable isotope values track the strength of the EUC. Our findings open up possibilities to extend the record of the EUC back in time with isotope-based paleoclimate proxies from the Galápagos region.Key PointsGalápagos seawater δ18O values strongly covary with equatorial cold tongue salinity valuesSeawater δ18O values are higher with a stronger Pacific Equatorial Undercurrent west of Galápagos Peer Reviewed ...